2014
DOI: 10.1007/s10616-014-9732-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of relationship between IL-6 gene variants and hypertension in Turkish population

Abstract: Hypertension (HT) is a common and life threating health problem worldwide leading to stroke, heart attack and renal failure. It is characterized by elevated blood pressure forced heart load. Human interleukin-6 (IL-6) and C-reactive protein (CRP) are known to be involved in inflammatory processes. IL-6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…We failed to detect any significant differences among ethnicities. Intuitively, our results were inconsistent with the previous meta-analysis by Niu et al 22 because our meta-analysis was superior due to the following reasons: first, we included more recently published studies, 11 , 16 , 74 , 75 which were not available at the time of the previous meta-analysis. Second, the −174 G>C polymorphism was rare in eastern Asian populations 94 and had a relatively high allele frequency in Caucasians (40%).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…We failed to detect any significant differences among ethnicities. Intuitively, our results were inconsistent with the previous meta-analysis by Niu et al 22 because our meta-analysis was superior due to the following reasons: first, we included more recently published studies, 11 , 16 , 74 , 75 which were not available at the time of the previous meta-analysis. Second, the −174 G>C polymorphism was rare in eastern Asian populations 94 and had a relatively high allele frequency in Caucasians (40%).…”
Section: Discussioncontrasting
confidence: 91%
“…Further exploration of the heterogeneity was conducted by Galbraith plots in 4 genetic models. We finally found that the studies by Karaman et al 74 and Jeng et al 76 were located outside of the 2 lines in the plots (Figure 5 ). After the studies by Jeng et al and Karaman et al were omitted from the corresponding models, all I 2 values decreased to less than 50% in all of the genetic models, and the pooled ORs and 95% CIs were not materially altered (data not shown).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The cytokine Interleukin-6 (IL-6) is a fundamental mediator of the acute-phase response to endothelial injury and regulates the production of C Reactive Protein (CRP) in hepatocytes [ 23 ]; therefore, both IL-6 and CRP genetic variants have been evaluated in relation to hypertension [ 2 , 20 ]. In the paper from Karaman et al [ 24 ], IL-6 rs1800795 and rs1800796 SNPs (MAF = 14.12% and 31.39%, respectively, 1000 Genomes) were genotyped in a Turkish sample of 108 controls and 111 hypertension patients. Both SNPs genotypes were not significantly related to hypertension or to IL-6 and CRP plasma levels.…”
Section: Resultsmentioning
confidence: 99%
“…This healthy problem is a highly complex genetic and multi-factorial disease that affected by genetic influences and environmental factors. Karaman et al reported that SNPs in candidate genes are susceptible to these multifactorial diseases [3]. Many reports with Asians showed us that a positive association detected between the 572 G / C polymorphism with CAD risk [27,28,33], while no such association in studies with Caucasian populations [21,23,24,25].…”
Section: Discussionmentioning
confidence: 99%